Evaluation of the long-term outcomes of the University of Michigan’s Practice-Oriented Research Training (PORT) program - Ianni, Phillip A.; Samuels, Elias M.; Eakin, Brenda L.; Champagne, Ellen; Kalpakjian, Claire Z.; Murphy, Susan L. (Journal of clinical and translational science, 2024)
The University of Michigan created the Practice-Oriented Research Training (PORT) program and implemented it between 2008 and 2018. The PORT program provided research training and funding opportunities for allied healthcare professionals. The program consisted of weekly didactics and group discussion related to topics relevant to developing specific research ideas into projects and funding for a mentored research project for those who submitted a competitive grant application. The goal of this evaluation was to assess the long-term impact of the PORT program on the research careers of the participants. Ninety-two participants (74 staff and 18 faculty) participated in both phases of the program. A mixed-methods approach to evaluation was used; 25 participants who received funding for their research completed surveys, and semi-structured interviews were conducted with eight program participants. In addition, data were collected on participants’ publication history. Fifteen out of the 74 staff participants published 31 first-authored papers after participating in PORT. Twelve out of 15 staff participants who published first-authored papers did so for the first time after participating in the PORT program. Results of quantitative and qualitative analyses suggest that the PORT program had positive impacts on both participants and the research community.